2018
DOI: 10.1007/s11104-018-3721-7
|View full text |Cite
|
Sign up to set email alerts
|

Identity of plant, lichen and moss species connects with microbial abundance and soil functioning in maritime Antarctica

Abstract: We provide evidence, from a comparative study, that plant and biocrust identity is associated with different levels of soil functioning and microbial abundance in Maritime Antarctica. Our results suggest that changes in the spatial distribution of these species linked to climate change could potentially entail changes in the functioning of Antarctic terrestrial ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 108 publications
2
13
0
Order By: Relevance
“…It has been reported that the fungal cell wall rigidity is due to a molecular complex formed by chitin and α-1,3-glucan (Kang et al 2018). Given the low nitrogen availability in this area (Benavent-González et al 2018) it seems that the strategy of H. lugubris would be to allocate this nutrient preferably in chitin, increasing thallus strength, than in algal cells (chlorophyll and rubisco, mainly), reducing productivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the fungal cell wall rigidity is due to a molecular complex formed by chitin and α-1,3-glucan (Kang et al 2018). Given the low nitrogen availability in this area (Benavent-González et al 2018) it seems that the strategy of H. lugubris would be to allocate this nutrient preferably in chitin, increasing thallus strength, than in algal cells (chlorophyll and rubisco, mainly), reducing productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to soil stabilization, biocrusts affect the cycling of carbon and nutrients, as well as the microbial communities living atop, around, and beneath them. Benavent-González et al (2018) showed that plant and biocrust identity were associated with different levels of soil functioning and microbial abundance in Antarctica. In particular, the activity of multiple enzymes varied by species and the authors observed positive correlations between soil nutrient availability and microbial abundance with biocrusts compared with bare soil.…”
Section: New Insights Into How Biocrusts Impact Ecosystem Functioningmentioning
confidence: 99%
“…pedogenetic and landform processes) determine the 14 pedoenvironments along Half Moon island (Figure 2, Supplementary Material -Text S1 and Table SIa of Appendix). Given the marked differences between pedoenvironments, we considered the habitat filtering approach for soil-species relationship analysis (Poelking et al 2015, Benavent-González et al 2018, Schmitz et al 2020. Thus, the possibility of a separating boundary between pedoenvironments provided an opportunity to study the effects of habitat filtering on species assemblages at a local scale in Maritime Antarctica (Poelking et al 2015).…”
Section: Selection Of Pedoenvironmentsmentioning
confidence: 99%